Penerapan Model Pembelajaran PjBL Berbasis Short Video Aplikasi Tiktok Pada Materi Perubahan Lingkungan Terhadap Pemahaman Konsep Dan Motivasi (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid advancement of digital technology has reshaped how students engage with science learning, especially in Generation Z. This study aims to examine the effectiveness of Project-Based Learning (PjBL) integrated with TikTok short video creation on students’ conceptual understanding and learning motivation in environmental change topics. Utilizing a quasi-experimental design with nonequivalent control group, 72 tenth-grade students were divided into an experimental class (PjBL + TikTok) and a control class (PjBL + PowerPoint). Data were collected through multiple-choice tests and motivation questionnaires. The findings reveal that the experimental group significantly outperformed the control group in both cognitive achievement and motivation levels. TikTok-based projects fostered student creativity, collaboration, and visual communication skills, while increasing learning satisfaction. These results indicate that integrating popular social media into PjBL enhances both cognitive and affective domains of learning. The study underscores the pedagogical potential of short-form video platforms to bridge formal education with digital habits, suggesting practical implications for 21st-century learning environments.